The Status of Public Sector Pay Equity for Women of Color in the United States. (December 2019) - Reese, Catherine C.
Research by Reese and Warner and Llorens, Wenger, and Kellough assesses the relative pay of women in the United States. However, research on the relative pay of women of color remains scant. What kinds of factors predict relative pay for women of color, and are they the same as for White women? The author utilizes ordinary least squares (OLS) regression on an Equal Employment Opportunity Commission (EEOC) panel data set on public sector employment by state to analyze the pay of Black, Hispanic, Asian, and American Indian women relative to men for 2005-2013. The author reaffirms that whether a woman lives in a state that has implemented a major gender pay equity measure is a significant factor determining her relative pay. Furthermore, the intersectional nature of public sector pay for women of color is numerically verified. Women fare better in states where they are descriptively represented in terms of gender and race/ethnic group.